Developing a new empathy-specific admissions test for applicants to medical schools: A discourse-pragmatic approach. (20th October 2017) - Pounds, Gabrina; Salter, Charlotte; Platt, Mary Jane; Bryant, Pauline
Abstract : The ability to empathise with patients is an important professional skill for doctors. Medical students practise this skill as part of their medical education, and are tested on their use of empathy within their final examination. Evidence shows that appropriate training makes a difference but that natural aptitude also plays a role. Most medical schools, therefore, probe applicants' basic understanding of empathy at admissions interviews. The purpose of the project presented in this paper was to apply existing understanding of how empathy may be communicated in a clinical context (building on a literature review by Pounds [2011]) to develop a new empathy-specific medical admissions interview station, probing applicants' empathic communicative performance (not just theoretical knowledge) and fitting the widely used Multiple Mini Interview (MMI) format. The paper outlines how this tool was developed, trialled and implemented by: (1) conceptualising empathic communication in discourse-pragmatic terms – that is, as a set of specific but context-dependant empathic speech acts; and (2) formulating and trialling a written and two oral versions of a situational test, capable of probing the applicants' ability to communicate empathically in everyday conversation and suitable for use at Norwich Medical School and other similar educational institutions.